Individual differences in spontaneous self-affirmation and mental health: relationships with self-esteem, dispositional optimism and coping. Issue 3 (3rd April 2023) - Harris, Peter R.; Richards, Alice; Bond, Rod
ABSTRACT: In two online studies, we test whether spontaneous self-affirmation (measured by the Spontaneous Self-Affirmation Measure, SSAM) predicts better mental health and coping and the role that self-esteem and dispositional optimism play in these relationships. Study 1 (N = 110) was cross-sectional. In study 2 (N = 192) we collected the mental health measures one month post-baseline. Consistent with pre-registered hypotheses, the SSAM predicted less anxiety, depression and avoidant coping, and greater wellbeing and non-avoidant coping; however, relationships involving self-esteem and optimism varied with the reported source of self-affirmation measured by the SSAM (strengths, values, social relations). Overall, the findings are generally consistent with the hypothesis that spontaneous self-affirmation tends to function as a resource that fosters positive coping with threats.